2017
DOI: 10.1016/j.prevetmed.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of Salmonella 1,4,[5],12:i:- shedding in five Australian pig herds

Abstract: The shedding patterns of Salmonella spp. and MLVA profiles of Salmonella enterica subspecies enterica (I) serotype 1,4,[5],12:i:- were monitored in a 12-month longitudinal observational study of five pig herds to inform management; provide indications of potential hazard load at slaughter; and assist evaluation of MLVA for use by animal and public health practitioners. Twenty pooled faecal samples, stratified by age group, were collected quarterly. When Salmonella was cultured, multiple colonies were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…Based on the reported short-term substitution rate of 1–2 SNPs per genome per year for Salmonella Typhimurium 60,72,73 , the common ancestor for farm-specific clusters existed in the last 2–7 years. This is also consistent with previous studies that used subgenomic typing methods 15,74,75 .…”
Section: Discussionsupporting
confidence: 93%
“…Based on the reported short-term substitution rate of 1–2 SNPs per genome per year for Salmonella Typhimurium 60,72,73 , the common ancestor for farm-specific clusters existed in the last 2–7 years. This is also consistent with previous studies that used subgenomic typing methods 15,74,75 .…”
Section: Discussionsupporting
confidence: 93%
“…Studies have reported that multidrug-resistant (MDR) S. Typhimurium phage type U 288, DT 120, and DT 193 are the most prevalent in swine (39,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) and DT 193 in both humans and pigs (62,72,73). Some researchers have suggested that the prevalence of phage type DT 193 has increased in humans over the past 10 years due to its association with the dominant clone of monophasic S. Typhimurium (39,(73)(74)(75)(76), although this clonal line is a heterogeneous phage type comprising different monophasic S. Typhimurium lineages (74). Similarly, DT 120 has been associated with the monophasic variant, although some DT 120 members have derived from DT 104 and are not monophasic (74).…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium (strain SO4698-09) carries a Salmonella genomic island (SGI) which contributes to enhanced resistance to copper sulfate, a common animal feed additive ( 3 ). We recently reported the genome sequence of S. enterica 1,4,[5],12:i:- strain TW-Stm6, an isolate recovered from pig feces which has the same antigenic formula, phage type, and sequence type as strain SO4698-09, and also carries the genomic island, SGI-4 ( 3 5 ). The assembled genome of TW-Stm6 comprised a 4,999,862-bp chromosome, a 4-kb MOB Q plasmid (pSTM6-4), and a 275.8-kb IncHI2 plasmid (pSTM6-275).…”
Section: Textmentioning
confidence: 99%